Alien Angiospermic Plants of Panna Tiger Reserve, Madhya Pradesh, India - Suman, N. R.; Khare, P. K.; Salunkhe, Onkar; Chadhar, Babulal (Indian Forester, 2017)
The paper deals with the enumeration of alien species of Panna Tiger Reserve of Madhya Pradesh, India. In all 75 alien taxa of angiosperms were found and enumerated with the correct botanical names, families, uses, source of origin, life form and their habitats. Cassia, Corchorus and Indigofera are the prominent genera while Asteraceae and Fabaceae are prominent families in the area. Tropical American component dominated the alien flora contributing 63% to the vegetation. Life formwise herbs were the major forms. Most of the alien species introduced to the area was unintentional; however, a number of them are used for various purposes.